Orientated inhibition of humin formation in efficient production of levulinic acid from cellulose with high substrate loading: Synergistic role of additives. (1st June 2023) - Hu, Ping; Hu, Yexin; Li, Hui; Li, Linzhen; Xue, Zhidan; Wu, Di; Zhao, Juan; Hu, Changwei; Zhu, Liangfang
Abstract: The main bottleneck in the direct conversion of cellulose to levulinic acid (LA), a promising bio-based platform chemical, lies in the severe formation of humins, especially at high substrate loading (>10 wt%). Herein, we report an efficient catalytic system consisting of a 2-methyltetrahydrofuran/water (MTHF/H2 O) biphasic solvent with NaCl and cetyltrimethylammonium bromide (CTAB) as additives for converting cellulose (15 wt%) to LA in the presence of a benzenesulfonic acid catalyst. We show that both NaCl and CTAB accelerated the depolymerization of cellulose and formation of LA. However, NaCl favored the humin formation via degradative condensations, whereas CTAB inhibited humin formation by restraining the routes of both degradative and dehydrated condensations. A synergistic role of NaCl and CTAB on suppressing humin formations is illustrated. The combined use of NaCl and CTAB led to an increased LA yield (60.8 mol%) from microcrystalline cellulose in MTHF/H2 O ( V MTHF / V H2O  = 2/1) at 453 K for 2 h. Moreover, it was efficient for converting cellulose fractioned from several kinds of lignocellulosic biomass, wherein a high LA yield of 81.0 mol% was achieved from wheat straw cellulose. This work presents a new strategy for advancing LA biorefinery by synergistically promoting cellulose depolymerization with orientated inhibition of undesired humin formation. Graphical abstract: Unlabelled Image